1982
DOI: 10.1002/bip.360210209
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin structure studied by linear dichroism at different salt concentrations

Abstract: SynopsisWe have studied the linear dichroism (LD) of rat liver chromatin oriented by flow. Soluble chromatin, prepared by brief nuclease digestion, is found to exhibit a positive LD at low ionic strength (1 mM NaCl), with a constant LDIA over the absorption band centered at 260 nm (A, isotropic absorbance). Several previous dichroism studies on soluble chromatin have been performed on sonicated materials and have given negative LD, probably due to the presence of uncoiled DNA. The positive dichroism can be int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
2

Year Published

1983
1983
1990
1990

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 39 publications
1
12
2
Order By: Relevance
“…Recently Tjerneld et al [15] reported a flow linear dichroisni study of rat liver chromatin at different salt concentrations. They found that the L D is positive at NaCl concentrations between 1 mM and IOOmM, while at concentrations higher than 0.5 M the LD signal was negative.…”
Section: _ -Imentioning
confidence: 99%
See 2 more Smart Citations
“…Recently Tjerneld et al [15] reported a flow linear dichroisni study of rat liver chromatin at different salt concentrations. They found that the L D is positive at NaCl concentrations between 1 mM and IOOmM, while at concentrations higher than 0.5 M the LD signal was negative.…”
Section: _ -Imentioning
confidence: 99%
“…The latter two methods have been extensively used to study the structure of both isolated nucleosomes and high-molecular-weight chromatin fragments. These methods, however, suffer from two serious disadvantages : (a) limited application to high-ionic-strength solutions, due to the thermal and electrochemical processes in the Kerr's cell, and (b) the electric field used for orientation of the molecules probably induces structural distortions in the chromatin fibrils [15,27]. These limitations can be overcome by flow orientation of the chromatin fibrils [15,16].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…LD reflects the average orientation of the light absorbing transition dipoles in a macroscopically oriented sample, and is expected to depend sensitively on the DNA arrangement in chromatin. Despite intense study, however, the interpretation of LD results on chromatin has been subject to a remaining ambiguity, since electrically oriented and flow oriented chromatin, in an intermediate range of ionic strengths, persistently show different features: flow LD (FLD) being positive (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and electric LD (ELD) generally negative (11,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). This incongruity has been suggested to reside in different preparation procedures, buffer conditions or in experimental artifacts (28).…”
mentioning
confidence: 93%
“…In solution linear dichroism has been applied to cases wherein DNA has been aligned by an electric field (Fredericq and Houssier, 1973;Mitra et al, 1984;McGhee et al, 1980) and flow (Tjerneld et al, 1982). The introduction of fluorescent labels which bind to DNA was an important improvement, because it increased the sensitivity of detection (Mitra et al, 1984;Kubista et al, 1985;Yoshida et al, 1987).…”
Section: Introductionmentioning
confidence: 99%